(untitled) (Baghdad Science Journal, 2005)
Were studied changes in the concentration of copper, iron and zinc in blood serum of one hundred patients with chronic kidney and treated dialysis blood were also measured the level of calcium kidney and phosphate Calciotropic in serum of these patients took samples of blood from these patients before and after treatment dialysis vessels as well as the statement of changes in those standards Alkimaahiatih Results were compared with twenty-five healthy people (control group)